Combinatorial Biobleaching of Mixedwood Pulp with Lignolytic and Hemicellulolytic Enzymes for Paper Making - Angural, Steffy (Indian J Microbiol, 2020)
Microbial enzymes are the safe alternatives to chemical based bleaching of pulp in paper mills. For effective biobleaching, both hemicellulolytic and lignolytic enzymes are required. This study reports laccase (L) + xylanase (X) and laccase (L) + mannanase (M) enzyme concoctions for pulp biobleaching derived from Bacillus sp. LX and Bacillus sp. LM isolated from the decaying organic matter. All enzymes were thermo-alkali-stable, hence were suitable for their application in pulp biobleaching. When a mixture of L + X/L + M was used for mixedwood pulp biobleaching, 46.32/40.25% reduction in kappa number; 13.21/10.01% and 3.36/2.76% improvement in brightness and whiteness was achieved respectively. Moreover, no laccase mediator system was required in the current process. Significant changes in the structure of enzymatically treated pulp were also observed. All these properties make these concoctions of enzymes suitable for their application in pulp and paper mill.